WP1-12 Reducing infection rates in an intrathecal baclofen service; closing the audit cycle. Issue 3 (14th February 2019) - Donnelly, A; Balaratnam, M; Murphy, M; Bahadur, S; Padilla, H; Keenan, E; Farrell, R; Stevenson, V
Abstract : Objectives: Intrathecal baclofen (ITB) is a recognised treatment strategy for the management of spasticity. We have 30 years of experience, and 160 patients currently receiving treatment. Design: An audit (Jan 13 – Jul 15) demonstrated complication rates of 4.4% (infection) and 4.92% (catheter). After this we recommended 1 vancomycin wash of the pump pocket, 2 occlusive dressing of pressure sores, 3 timely MRSA pre-screening, and this was introduced June-August 2016. We present a re-audit of the service. Subjects: All patients admitted for ITB pump surgery between June 2016 and June 2018. Methods: The database of patients was used, from which the patient notes were reviewed with information relating to each surgical procedure recorded. Results: There were 92 surgical procedures and 78 patients (M 30, F 48). 12 patients had complications, requiring 18 surgical procedures. Out of 18 surgical procedures, 10 were catheter- and 7 pump-related). Our infection rate was lower at 1% of all surgeries (compared with 4.4%), or 0.6% of all ITB pump patients per year (compared with 3.4%), and our catheter complication rate was 6.25% of all patients per year. Our annual incidence rate of all complications was 5.6% in both groups. Conclusions: The infection risk is lower and complication rate remains stable. We will discuss factors which may influence the risk of complication, and consider recommendations for the future.